Framing Biotechnology: A Comparison of U.S. and British National Newspapers - Lisa K. Lundy; Tracy A. Irani (Journal of Applied Communications, 2004)
Despite the potential promise of agricultural biotechnology, consumers’ trust and acceptance varies in some parts of the world. To develop a deeper understanding of the differences in news media coverage of agricultural biotechnology in U.S. and British newspapers, a framing analysis study was conducted, focusing on the news coverage of three major national “newspapers of record” during the calendar year 2002: The New York Times, The Washington Post, and The Guardian. No single frame was dominant in U.S. or British national newspaper coverage of agricultural biotechnology in 2002. Some of the prominent frames were contamination of the food supply, human risk, environmental risk, scientific progress, and world hunger. There were more different frames used in The Guardian (concepts as consumer choice, dependency, and politics) than in the U.S. newspapers. Additionally, this study reiterated findings that British news coverage included more editorial coverage of agricultural biotechnology.